Hybrid rice achievements, development and prospect in China - Guo-hui MA; Long-ping YUAN (Journal of Integrative Agriculture, 2015)
This article reviews the history and progress of hybrid rice development. Hybrid rice research was initiated back in 1964, and commercialized in 1976. Three-line and two-line system hybrid rice were developed in 1974 and 1995, respectively. Research on super hybrid rice, which was first launched by Ministry of Agriculture, China in 1996, is discussed, and the great progress of super hybrid rice had been achieved with a new yield record by 15.4 t ha−1 in the 6.84 ha demonstration location in Xupu, Hunan Province, China in 2014. And the mechanism of heterosis, the techniques of hybrid seed production and the modern field managements in hybrid rice over the past decades are also discussed. Additionally, this article dealt with the intellectual property protection (IPR) and development of hybrid rice seed industry in China. Major factors that constrain hybrid rice development are analyzed and possible solutions to this problems are proposed. Finally, the authors present methods to further increase production yield, and propose an improvement for breeding super high-yielding hybrid rice based on these methods.